Physical Therapies for Psychosomatic Symptoms and Quality of Life Induced by Aromatase Inhibitors in Breast Cancer Patients: A Systematic Review and Meta-Analysis - Zhu, Xue-Ying; Li, Zhong; Chen, Cong; Feng, Ru-Li; Cheng, Bai-Ru; Liu, Ruo-Yi; Wang, Rui-Ting; Xu, Li; Wang, Yue; Tao, Xin; Zhao, Peng (Frontiers in Oncology, 2021)
Objective To evaluate the effects of Physical Therapies (PTs) on improvement in psychosomatic symptoms and quality of life (QOL) in breast cancer patients. Data Sources Seven databases (MEDLINE, EMBASE, Cochrane CENTRAL, China National Knowledge Infrastructure, Wangfang, VIP, and China Biology Medicine disc databases) were systematically searched from the database inception through May 18, 2021. Study Selection Randomized controlled trials (RCTs) which compared acupuncture or exercise with a sham control or usual care for the treatment of aromatase inhibitors (AIs)-related psychosomatic symptoms and QOL. Data Extraction and Synthesis Data were screened and extracted independently using predesigned forms. The quality of RCTs was assessed with the Cochrane Handbook for Systematic Reviews of Interventions. The effect size was calculated via random-effects modeling. The quality of evidence was evaluated with the Grading of Recommendations Assessment, Development and Evaluation approach. Main Outcomes and Measures The score of pain was measured with BPI scale and Western Ontario and the McMaster Universities Index (WOMAC) scale. Emotional state was measured with Pittsburgh Sleep Quality Index (PSQI), Hospital Anxiety and Depression Scale (HADS-A), and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue). The QOL score was measured by self-reported measurements, including the Functional Assessment of Cancer Therapy-General (FACT-G) scale and 36-Item Short Form Survey (SF-36) scale. Results Eleven RCTs (with 830 patients) were included in the systematic review, and data from 10 RCTs (with 798 patients) were used in the meta-analysis. Results showed acupuncture significantly reduced worst pain scores (P < 0.00001, I2 = 83.5%) [SMD = −0.81, 95% CI (−1.51, −0.11)], but the effect of exercise therapies was not significant in overall change in worst pain scores (P =0.006, I2 = 72.3%) [SMD = −0.30, 95% CI (−0.76, 0.16)]. Both acupuncture and exercise resulted in little to no difference in overall change in HADS-A subscale (P = 0.026<0.05, I2 = 79.8%) [WMD = −0.21, 95% CI (−3.44, 3.03)], PSQI subscale (P = 0.488, I2 = 0%) [WMD = 0.98, 95% CI (−0.57, 2.53)], and FACIT-Fatigue subscale (P = 0.022<0.05, I2 = 81.0%) [WMD = 1.6, 95% CI (−5.75, 8.94)]. Exercise (compared with usual care) was associated with improving overall change in health-related QOL (subscales of SF-36 tool) (P = 0, I2 = 72.1%) [WMD = 7.97, 95% CI (5.68, 10.25)] and cancer-specific QOL (subscales of FACT-G tool) (P = 0.304, I2 = 16%) [WMD = 1.16, 95% CI (0.34, 1.97)]. Conclusions and Relevance This systematic review and meta-analysis suggested that based on moderate-level evidence, acupuncture was associated with significant reductions in pain intensity, and exercise might improve QOL in breast cancer patients treated with AIs. However, in psychosomatic symptoms such as anxiety, sleep disturbance, and fatigue, acupuncture and exercise training did not result in significant improvements.